The Pseudomonas quinolone signal (PQS) stimulates chemotaxis of polymorphonuclear neutrophils: $hGertrud M. Hänsch, Birgit Prior, Gerald Brenner-Weiss, Ursula Obst, Joerg Overhage - Hänsch, Gertrud Maria; Prior, Birgit; Brenner-Weiss, Gerald; Obst, Ursula; Overhage, Joerg (Journal of applied biomaterials & functional materials, 2014)
Cross-talk between bacteria and mammalian cells is increasingly recognized as an important factor, especially during chronic infections. In particular, the inte...
Gesehen am 24.09.2020